A study on handling equipments operation and performance at Port Klang-KPCT Sdn Bhd / Azahari Ramli - Ramli, Azahari (1996)
In year 2010, Port Klang is expected to serve as a hub port or load centre for all cargo entering, leaving and transiting the Straits of Malacca area. Klang Port Container Terminal ( KPCT ) Sdn Bhid should be well prepared in term of handling facilities in order to face the challenge in the future. The numbers of handling equipments are not just determined the level of throughput but the level of service guarantee by the port operator. The performance and operation of the handling facilities must in position in meeting client's requirements. The purpose of the study is to determine whether the present operation and performance of handling equipments can cope the demand in the future. Whether the present numbers of handling equipments available are sufficient to cater the demands. The study proved that the current operation and performance of the handling equipments are not sufficient to meet the demand in the future and the present number of the handling machine only adequate in meeting today requirement. Solution to the problem will be presented at the end of the chapter. It is essential to present adequate facilities with appropriate method of operation and efficient performance in meeting the challenge.